Posterior cortical dementia with alexia: neurobehavioural, MRI, and PET findings. Issue 5 (May 1991) - Freedman, L; Selchen, D H; Black, S E; Kaplan, R; Garnett, E S; Nahmias, C
Abstract : A progressive disorder of relatively focal but asymmetric biposterior dysfunction is described in a 54 year old right handed male. Initial clinical features included letter-by-letter alexia, visual anomia, acalculia, mild agraphia, constructional apraxia, and visuospatial compromise. Serial testing demonstrated relentless deterioration with additional development of transcortical sensory aphasia, Gerstmann's tetrad, and severe visuoperceptual impairment. Amnesia was not an early clinical feature. Judgment, personality, insight, and awareness remained preserved throughout most of the clinical course. Extinction in the right visual field to bilateral stimulation was the sole neurological abnormality. Early CT was normal and late MRI showed asymmetrical bioccipitoparietal atrophy with greater involvement of the left hemisphere. Results from positron emission tomography (PET) showed bilaterally asymmetric (left greater than right) occipitotemporoparietal hypometabolism. The metabolic decrement was strikingly asymmetric with a 50% reduction in glucose consumption confined to the left occipital cortex. The picture of occipitotemporoparietal compromise verified by MRI, PET, and neurobehavioural testing would be unusual for such degenerative dementias as Alzheimer's (AD) and Pick's disease, although atypical AD with predominant occipital lobe involvement cannot be excluded. This case supports the concepts of posterior cortical dementia (PCD) as a clinically distinct entity and for the first time documents its corresponding metabolic deficit using PET.